Manajemen Pembelajaran di Madrasah Aliyah Pondok Pesantren Pancasila Kota Bengkulu - Abdullah Abdullah (Program Magister Manajemen Pendidikan Islam Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 1970)
This study aims to describe the conditions of the implementation of teaching and learning activities in Madrasah Aliyah Pancasila and reveal the conditions of studentsboth before learning and after learning. Through this research, a complete picture of the teaching implementation process in Madrasah Aliyah Pancasila is obtained, in which the activity and creativity of teachers as teaching staff, infrastructure support and student activity are required. The study used a qualitative approach, using data collection instruments in the form of: questionnaires, interviews and documentation. The aim of this research is to explore important scientific findings from the conditions of teaching and learning activities in the Madrasah Aliyah Pancasila studied, and then look for learning models that pay more attention to the quality / quality of teaching staff, the quality of student input, support of facilities and support of other factors. The results of this study conclude that: (1) The teaching process has not gone well due to the use of less varied teaching methods so that teaching becomes less attractive, (2) A decrease in the quality of output because the teachers have not carried out their teaching assignments professionally, (3) Factors factors which become obstacles / constraints in teaching, namely the quality of input / students that are still low, the sense of responsibility of teachers who are still lacking, communication that has not been running and the lack of infrastructure.